Mentoring practices in radiologic science education. - Kowtko C (Radiologic Technology)
BACKGROUND: Mentoring in health science education programs has gained popularity over the past 20 years and is associated with increased self-confidence and self-esteem and decreased stress and anxiety. OBJECTIVE: To determine the extent of mentoring practices within the radiologic sciences. METHODS: An online survey was administered to 125 radiography programs in the southeastern United States accredited by the Joint Review Committee on Education in Radiologic Technology. RESULTS: Of the 36 respondents, only 22% had formal mentoring programs. The majority believed their mentoring program had a positive effect on student retention and was somewhat successful. CONCLUSION: Future research involving a larger population of radiologic science programs would be beneficial.